The Collision of Regulatory Convergence and Divergence: Updating Policies of Surveillance and Information Technology - Hosein, Ian (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2001)
Regulation theory rarely considers the disruptive capacity of technology, nor regulation in the sole interest of government. This paper will investigate the capacity of technology to disrupt regulatory regimes surrounding surveillance and communications infrastructure in various countries. As policy regimes are updated to meet new challenges, through the creation of new policy habitats, new powers are created despite protests and claims of technological neutrality. However, the capacity to interpret technology does not end: technology will disrupt even the new habitat, requiring renegotiation and re-settlements. Such negotiations often occur at the international level; some of these processes will be reviewed and critiqued. Considering the contingent nature of technology policy, this paper then recommends some ways forward when considering new national policies, such as the process that South Africa is about to embark on.